TEKS DRAMA GONG SAMPIK ANALISIS BENTUK, FUNGSI, DAN MAKNA - Sugita, I Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Research on the â€œText Drama Gong Sampik Analysis Form , Function , and Meaningâ€, aimed to describe the structure of the building as well as the text examines the function and meaning of the text contained in the drama gong â€œSampikâ€ . This research uses , semiotic theory (Enraswara , 2008: 64) , the theory of the structure , (Teeuw , 1984: 135) . The method used in the stage of providing data using methods refer to the technical note . In addition, using interviews with recording techniques and record . Furthermore, in the stage of data analysis using descriptive analytic techniques are also used literally and idiomatically . At the stage of presentation of the data , the method used is an informal method of inductive and deductive techniques . The results showed that ; (1) analyzes the structure of the text form of drama that builds drama gong â€œSampikâ€ There are four, namely : prologue , stage , scenes , and dialogue, and the narrative structure of the play there are five: plot, characterization and characterization , setting , theme, and mandate. (2) the language and style of the language used in the text of the drama gong â€œSampikâ€. (3) text functions drama gong â€œSampikâ€ there are some functions that are contained in each babaknya quote quote that reflects situation or social reality. (4) the meaning of the text drama gong â€œSampikâ€ This is a search for identity .